The Implementation of Using Webtoon Media to Improve Eleventh-Grader Students’ Vocabulary Achievement - Kamila Ramadhanti; Endang Mastuti Rahayu (Edu-Ling: Journal of English Education and Linguistics, 2025)
The research aimed to explore the application of Webtoon media in increasing the vocabulary achievement of grade 11 students at SMAN 1 Karangbinangun. This was because learning had been perceived as boring, which made it difficult for students to memorize vocabulary. The lack of technology integration in learning contributed to this issue. The research employed the classroom action research method. It was carried out in two cycles. Data collected through observation sheets, tests, and questionnaires indicated significant enhancement in students' vocabulary achievement. The research results showed that in cycle 1 and cycle 2, students achieved a score of >75, with 0% of students in the pre-test, 25% in post-test 1, and 84% in post-test 2. Furthermore, the results of observations and questionnaires revealed that the use of Webtoon media had helped improve students' vocabulary mastery. The study concluded that Webtoon media, combined with contextualized vocabulary activities, effectively enhanced students’ engagement, creativity, and knowledge. It not only motivated students but also supported the integration of technology and materials in English language teaching.